Manajemen anestesi pada ablasio retina: laporan kasus - Wina Nazula Makrufa (SEHATI: Jurnal Kesehatan, 2022)
Retinal detachment is a separation between retinal photoreceptor layer and retinal epithelial layer below. Retinal detachment happens in 67% people with myopia. Retinal detachment also happens in people with cataract surgery history and blunt trauma in the eye. Patients with retinal detachment may present with a history of photopsia. The patient also presents with visual field loss, usually starts in the periphery, and then moving to the central. Physical examination can be done with fundoscopy examination that may present with a retinal detachment if the eye was moving. Radiological examination can be done to support the diagnosis. Management of retinal detachment is by vitrectomy to lift up the material that causing traction, subretinal internal liquid drainage, and injection of air or gasses to maintain retinal position. A man aged 53 years old come with visual loss in the right eye. Patient felt that there is a foreign object in his right eye, so the patient rub his right eye to release the foreign object. Patient’s right eye only can see blurred from the side, but in the central he can not see anything. The physical examination presents with a retinal detachment in the right eye. Patient has controlled hypertension. There is no previous allergic or operative history. The patient receives an operative vitrectomy with general anesthesia. The patient receives preoperative, intraoperative, and postoperative to support the surgery..